Concurrent IDH1 and IDH2 mutations in glioblastoma: A case report - Haider, Ali S.; Ene, Chibawanye I.; Palmisciano, Paolo; Haider, Maryam; Rao, Ganesh; Ballester, Leomar Y.; Fuller, Gregory N. (Frontiers in Oncology, 2023)
Isocitrate dehydrogenase (IDH) mutations are cornerstone diagnostic features in glioma classification. IDH mutations are typically characterized by mutually exclusive amino acid substitutions in genes in the genes encoding for the IDH1 and the IDH2 enzyme isoforms. We report our institutional case of a diffuse astrocytoma with progression to secondary glioblastoma and concurrent IDH1/IDH2 mutations. A 49-year-old male underwent a subtotal resection of a lobular lesion within the right insula in 2013, revealing a WHO grade 3 anaplastic oligoastrocytoma, IDH1 mutated, 1p19q intact. Symptomatic tumor progression was suspected in 2018, leading to a surgical tumor biopsy that demonstrated WHO grade 4 IDH1 and IDH2 mutant diffuse astrocytoma. The patient subsequently underwent surgical resection followed by medical management and finally died in 2021. Although concurrent IDH1/IDH2 mutations have been rarely reported in the current literature, further study is required to better define their impact on patients’ prognoses and their response to targeted therapies.